Reseña de El alma de los objetos. Minificciones, de Ramón Gómez de la Serna. Ed. Rafael Cabañas Alamán. León: Eolas, 2019. ISBN: 978-84-17315-94-8 - Raquel de la Varga Llamazares (Microtextualidades, 2019)
Reseña de El alma de los objetos. Minificciones, de Ramón Gómez de la Serna